Perbandingan Proses Penyelesaian Tindak Pidana Pencemaran Nama Baik di Indonesia dan Australia - Muhammad Zhafran Rahman; Hafrida Hafrida; Mohamad Rafiq (PAMPAS: Journal of Criminal Law, 2022)
This study tries to explore and analyze the similarities and differences as well as the pros and cons of the settlement process in criminal acts against defamation in Indonesia and Australia. By tracing legal sources of both countries, this study demonstrates that the process of resolving criminal acts of defamation in Indonesia and Australia has several similarities and differences. The similarity rests on the application of two ways of criminal settlements, either by litigation or without litigation. In Indonesia, the settlement of defamation cases is always the domain of criminal law. In such the cases, according to the provisions of the Criminal Procedure Code, a complaint from the victim has to be brought to the Police in order to be set in the court. However, the defamation settlement can also be alternatively conducted through a non litigative way, known as a Restorative Justice system. Whereas in Australia, the settlement of criminal acts of defamation shall be resolved through civil proceedings, after which can be settled through criminal courts recommended with a written approval from the Director of Public Prosecutors.   ABSTRAK                                        Artikel ini bertujuan untuk mengetahui dan menganalisis persamaan dan perbedaan, berikut keunggulan dan kelemahan penyelesaian tindak pidana pencemaran nama baik di Indonesia dan Australia. Dengan menelusuri sumber-sumber bahan hukum kedua negara, artikel ini menunjukkan bahwa penyelesaian tindak pidana pencemaran nama baik di Indonesia maupun Australia memiliki beberapa persamaan dan perbedaan. Persamaannya terletak  pada diterapkannya dua jalur penyelesaian tindak pidana pencemaran nama baik, melalui pengadilan ataupun di luar pengadilan. Namun di Indonesia penyelesaian tindak pidana selalu merupakan ranah hukum pidana, yaitu dimulai dengan adanya pengaduan oleh pihak yang dirugikan ke pihak kepolisian sesuai dengan yang diatur dalam KUHAP. Penyelesaian melalui jalur Restorative Justice juga dapat diterapkan dalam proses penyelesaian pencemaran nama baik ini. Sedangkan di Australia, penyelesaian tindak pidana pencemaran nama baik justru harus diselesaiakan melalui jalur perdata terlebih dahulu, baru setelah itu dapat diselesaikan melalui jalur pidana dengan adanya persetujuan tertulis dari Direktur Penuntut Umum.